2009
DOI: 10.1161/atvbaha.109.185801
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin Induces EGF Receptor Expression and Cell Proliferation via a PKC(δ)/c-Src-Dependent Pathway in Vascular Smooth Muscle Cells

Abstract: Objection-Thrombin upregulates expression of several proteins in vascular smooth muscle cells (VSMCs) which may contribute to atherosclerosis. Here, we investigated the mechanisms underlying thrombin-induced EGF receptor (EGFR) expression and its effect on VSMCs. Methods and Results-Normal rat VSMCs were used. First, Western blotting and RT-PCR analyses showed that thrombin induces the expression of EGFR at transcription and translation levels in VSMCs. Second, pharmacological inhibitors, dominant negative mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 43 publications
2
38
0
6
Order By: Relevance
“…In addition to this important JNK/AP-1 pathway, thrombin may act upon VSMCs through several other signaling pathways. Thrombin enhanced VSMC proliferation through epidermal growth factor receptor, ERK, and AP-1 pathways [41] . Thrombin also stimulated VSMC migration through an ROS-sensitive p38 MAPK pathway [42] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this important JNK/AP-1 pathway, thrombin may act upon VSMCs through several other signaling pathways. Thrombin enhanced VSMC proliferation through epidermal growth factor receptor, ERK, and AP-1 pathways [41] . Thrombin also stimulated VSMC migration through an ROS-sensitive p38 MAPK pathway [42] .…”
Section: Discussionmentioning
confidence: 99%
“…Thr, a key player in the 'coagulation-atherogenesis' maze [10], exerts most of its proliferating effects though PAR-1 in VSMCs [17,29] and through direct proteolytic action, such as activation of pro MMP-2 that further supports VSMCs proliferation [30][31][32]. It is interesting to note here that Thr being capable of activating pro MMP-2 to MMP-2 under the association with heparin sulfate proteglycan, becomes a potent extracellular degrading enzyme [31].…”
Section: Thr-induced Vsmcs Proliferationmentioning
confidence: 75%
“…Thr has also been associated with VSMCs proliferation, including mesenchymal cells [14,15] and human fibroblasts [16] through activation of its proteolytically activated receptors (PARs). Thr is a G-protein coupled receptor (GPCR) agonist that stimulates phospholipase C and results in intracellular Ca 2+ elevation and protein kinase C (PKC) activation and these events participate in the stimulation of extracellular signal-regulated protein kinase p42/44 (ERK1/2) cascade [17,18]. In several cell lines, it has been shown that Thr mediates cell proliferation through transactivation of the epidermal grown factor receptor (EGFR) via a metalloproteinasemediated cleavage and release of pro-heparin binding EGF-like factor (pro HB-EGF), which then binds to EGFR [15,19,20].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism leading to increased expression of VEGFR2 in response to MMP-1 stimulation was also investigated in this study. It was previously shown that thrombin (a main activator of PAR-1) is able to stimulate NF-B and cause the up-regulation of multiple receptors (36,37). NF-B has also been shown to mediate KDR transcription (38).…”
Section: Discussionmentioning
confidence: 99%